Life-cycle environmental assessment of solar-driven Multi-Effect Desalination (MED) plant - Mohamed Alhaj (17151073) (2022)
Seawater desalination supplies 97 million m3 of freshwater daily to more than 300 million people worldwide. The global desalination market is dominated by two technologies, thermal and membrane desalination. These processes have adverse impacts on the environment in the form of harmful emissions into the air and water and also on human health. Therefore, our main research questions are: to what extent can we minimize the life cycle environmental impact of conventional thermal desalination processes through the integration of concentered solar power collectors, and how do various collectors compare in this regard? We answered these questions by conducting a life-cycle assessment (LCA) study on an optimized solar-driven multi-effect desalination (MED) process. The LCA results revealed that most of the life-cycle impact in the climate change, fossil depletion, and water depletion categories occurs during the operation phase based on electric pumping energy. The solar-driven process reduces climate change impact by 10 kg-CO2 eq., for every 1 m3 of freshwater as compared to the conventional one. We also found that the linear Fresnel collector has a better LCA rating than the parabolic trough collector. The broader implications of this work pertain to renewable energy and water resources policymaking and resource conservation. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2021.115451